Development of Korean Herbal Medicine Cosmetics Containing Polygonum Multiflorum Extracts (Medico Legal Update, 2019)
cosmetics that can improve aging skin of middle-aged women through the analysis of anti-oxidation and anti-aging using domestic PolygonumMultiflorum.Method: Extraction, anti-aging and antioxidant experiments were designed and performed by synthesizing previous studies based on scientific evidence and a prescription in Donguibogam (Treasured Paragon of Eastern Medicine) that utilized PolygonumMultiflorum for regaining vigor and rejuvenating at an old age.Findings: The result of this study showed that PolygonumMultiflorum presented high anti-oxidation effect from the analysis of Polyphenol, Flavonoid, and DPPH and it also has an excellent inhibiting ability, showing great possibility to be used as a material for functional cosmetics. Moreover, it showed a significant synergy effect in composites mixed with other raw materials at a small mixing quantity.Improvements/Applications: it has a great potential to be developed as a natural material for complex cosmetics in future